Efficacy and Safety of a Combination of Sabal and Urtica Extract in Lower Urinary Tract Symptoms - Engelmann, Udo; Walther, Carola; Bondarenko, Boris; Funk, Petra; Schläfke, Sandra (Arzneimittelforschung, 2006)
The aim of this prospective, randomized, double-blind, double-dummy, multicenter clinical trial was to investigate the efficacy and safety of PRO 160/120 (Prostagutt® forte), a fixed combination preparation of 160 mg Sabal fruit extract WS® 1473 and 120 mg Urtica root extract WS® 1031 per capsule, in comparison to the α1-adrenoceptor antagonist tamsulosin (CAS 106463-17-6) in lower urinary tract symptoms (LUTS) caused by benign prostatic hyperplasia (BPH).140 elderly out-patients suffering from LUTS caused by BPH, with an initial score ≥ 13 points in the International Prostate Symptom Score (I-PSS), received 2 × 1 capsule/d PRO 160/120 or 1 × 0.4 mg/d tamsulosin and were treated for 60 weeks with interim visits at weeks 8, 16, 24, 36, and 48.The primary outcome measure for efficacy was the change in I-PSS total score, the percentage of patients with an I-PSS score ≤ 7 points at endpoint ('re-sponders') was analyzed as well.During 60 weeks of randomized treatment the I-PSS total score was reduced by a median of 9 points in both groups. In total, 32.4 % of the patients in the PRO 160/120 group and 27.9 % in the tamsulosin group were responders (test for non-inferiority of PRO 160/120: p = 0.034; non-inferiority margin 10 %). Both drugs were well tolerated, with one adverse event in 1514 treatment days for PRO 160/120 and one event in 1164 days for tamsulosin.The study supports non-inferiority of PRO 160/120 in comparison to tamsulosin in the treatment of LUTS caused by BPH.
Keywords: International Prostate Symptom Score; Lower urinary tract symptoms; Prostagutt® forte; Sabal fruit extract, clinical trial, efficacy; Urologic drugs; Urtica root extract, clinical trial, efficacy; WS® 1031; WS® 1473